Feeding a family of five: Role Playing the Great Depression - Riney-Kehrberg, Pamela (Teaching History: A Journal of Methods, 1997)
In the spring of 1989, I drove hundreds of miles of back roads in Kansas, interviewing survivors of the dust bowl and Great Depression for my doctoral dissertation. I asked these people, ranging in age from their mid-sixties to nineties, many questions about their lives during the 1930s, including work and attitudes toward federal aid, and why they had stayed in Kansas when so many had left and gone to California. I also asked a number of questions about the "nuts and bolts" of life during hard times, such as how they or their parents made family food dollars stretch. Reflecting back on those difficult years, many commented that they, unlike the current generation of young people, had what it took to survive such calamities. Young people today, they reckoned, would collapse under the strain of providing for a family on such meager resources. 1